HUBUNGAN SARAPAN PAGI DENGAN PRESTASI BELAJAR SISWA DI SMA NEGERI 4 KOTA JAMBI TAHUN 2020 - Riska Marvelia; Rini Kartika; Hasna Dewi (Universitas Jambi, 2021)
ABSTRACT Breakfast has an important role in meeting the energy needs of student, because it can increase learning concentration and make it easier to absorb lessons at school, so that learning achievement is good. The research objective was to determine the relationship between breakfast and student academic achievement levels in Senior High School 4 Jambi City in 2020. This research is an analytic survey research with cross sectional design. The population is students who sit in class X MIPA and X IIS at Senior High School 4 Jambi City in 2020. The sample of simple random sampling technique is 110 people. This research was conducted at Senior High School 4 Jambi City in July-August 2020 in 2020 by direct interviews using a questionnaire. Data were analyzed by univariate and bivariate.The results of univariate analysis showed that 34 respondents (30.9%) had good breakfast, 43 respondents (39.1%) were sufficient, and 33 respondents (30.0%) were lacking. As for the description of study achievement, 59 respondents (53.6%) were good, 45 respondents (40.9%) were sufficient and 6 respondents (5.5%) were less. The bivariate results showed a significant relationship between breakfast and student achievement with a p-value (0.014). There is a significant relationship between breakfast and student achievement. Breakfast is useful in increasing learning concentration and memory when studying at school so that it will result in better achievement Keywords: Breakfast, study achievement ABSTRAK Sarapan pagi mempunyai peranan penting dalam memenuhi kebutuhan energi anak sekolah, karena dapat meningkatkan konsentrasi belajar dan memudahkan menyerap pelajaran di sekolah, sehingga prestasi belajar menjadi baik. Tujuan penelitian untuk mengetahui hubungan sarapan pagi dengan tingkat prestasi belajar siswa di SMA Negeri 4 Kota Jambi Tahun 2020. Penelitian ini merupakan penelitian survey analitik dengan rancangan cross sectional. Populasi adalah adalah siswa yang duduk di kelas X MIPA dan X IIS di SMA Negeri 4 Kota Jambi Tahun 2020. Sampel teknik simple random sampling yang berjumlah 110 orang. Penelitian ini dilakukan di SMA Negeri 4 Kota Jambi bulan Juli–Agustus 2020 tahun 2020 dengan wawancara langsung menggunakan kuesioner. Data dianalisis secara univariat dan bivariat. Hasil analisis univariat didapatkan gambaran untuk sarapan pagi sebanyak 34 responden (30,9%) baik, 43 responden (39,1%) cukup, dan 33 responden (30,0%) kurang. Sedangkan untuk gambaran prestasi belajar didapatkan sebanyak 59 responden (53,6%) baik, 45 responden (40,9%) cukup dan 6 responden (5,5%) kurang. Hasil bivariat terdapat hubungan yang bermakna antara sarapan pagi dengan prestasi belajar siswa dengan p-value (0,014). Terdapat hubungan yang bermakna antara sarapan pagi dengan prestasi belajar siswa. Sarapan berguna dalam meningkatkan konsentrasi belajar dan daya ingat ketika belajar di sekolah sehingga akan menghasilkan prestasi yang lebih baik. Kata Kunci : Sarapan pagi, Prestasi belajar